Rapid quantification of quinine by multi‐stacking in a portable microchip electrophoresis system. Issue 3 (26th November 2018) - Tai, Chee Tung; See, Hong Heng
Abstract: A new multi‐stacking pre‐concentration procedure based on field‐enhanced sample injection (FESI), field‐amplified sample stacking, and transient isotachophoresis was developed and implemented in a compact microchip electrophoresis (MCE) with a double T‐junction glass chip, coupled with an on‐chip capacitively coupled contactless conductivity detection (C 4 D) system. A mixture of the cationic target analyte and the terminating electrolyte (TE) from the two sample reservoirs was injected under FESI conditions within the two sample‐loading channels. At the double T‐junction, the stacked analyte zones were further concentrated under field‐amplified stacking conditions and then subsequently focused by transient‐isotachophoresis and separated along the separation channels. The proposed multi‐stacking strategy was verified under a Universal Serial Bus (USB) fluorescence microscope employing Rhodamine 6G as the model analyte. This developed approach was subsequently used to monitor the target quinine present in human plasma samples. The total analysis time for quinine was approximately 200 s with a sensitivity enhancement factor of approximately 61 when compared to the typical gated injection. The detection and quantification limits of the developed approach for quinine were 3.0 μg/mL and 10 μg/mL, respectively, with intraday and interday repeatability (%RSDs, n = 5) of 3.6 and 4.4%. Recoveries in spiked human plasma were 98.1–99.8%.